An Update on the Implications of New Psychoactive Substances in Public Health - Simão, Ana Y.; Antunes, Mónica; Cabral, Emanuel; Oliveira, Patrik; Rosendo, Luana M.; Brinca, Ana Teresa; Alves, Estefânia; Marques, Hernâni; Rosado, Tiago; Passarinha, Luís A.; Andraus, Maristela; Barroso, Mário; et al. (International journal of environmental research and public health, 2022)
The emergence of new psychoactive substances has earned a great deal of attention, and several reports of acute poisoning and deaths have been issued involving, for instance, synthetic opiates. In recent years, there have been profound alterations in the legislation concerning consumption, marketing, and synthesis of these compounds; rapid alert systems have also been subject to changes, and new substances and new markets, mainly through the internet, have appeared. Their effects and how they originate in consumers are still mostly unknown, primarily in what concerns chronic toxicity. This review intends to provide a detailed description of these substances from the point of view of consumption, toxicokinetics, and health consequences, including case reports on intoxications in order to help researchers and public health agents working daily in this area.